The Influence of Farmer Entrepreneurial Competence on Broiler Farm Performance in Bogor - Burhanuddin Burhanuddin; Rizky Prayogo Ramadhan (Jurnal Manajemen & Agribisnis, 2019)
The broiler is a highly demanded animal protein source for Indonesian people. Nowadays, primary and derived product demand for broiler chicken increases steadily. So it is necessary to increase broiler farm performance in order to meet the increased demand. One of the broiler farm centers which have fulfilled the rapid request of broiler chicken is located in Bogor, West Java. However, there was an important issue facing the broiler industry in Bogor, namely the decreased growth of broiler chicken population in Bogor. This indicates in the optimized business performance of broiler farm, impacting on business sustainability. Theoretically, business performance can be improved by stimulating farmer entrepreneurial competence. This study aimed to analyze factors affecting entrepreneurial competencies of farmers and determine the influence of farmer entrepreneurial competence on broiler farm performance in Bogor. This study used a convenience sampling method involving 120 contract farmers when running their business. Data were analyzed using descriptive method and multivariate analysis using structural equation modeling (SEM). The results showed that farmer entrepreneurial competencies were very dominant in broiler farm business performance. The entrepreneurial competence variable was mostly influenced by the managerial competence variable of farmers. The influential manifested variable to increase managerial competence was the farmer's ability in human resource management.Keywords: broiler farm, business performance, entrepreneurial competencies